Reconstructing Earth's Climate History : Inquiry-based Exercises for Lab and Class - John, Kristen St.; John, Kristen St. (West Sessex : Wiley-blackwell, 2012)
The context for understanding global climate change today lies in the records of Earth$1 (Bs past. This is demonstrated by decades of paleoclimate research by scientists in organizations such as the Integrated Ocean Drilling Program (IODP), the Antarctic Geological Drilling Program (ANDRILL), and many others.The purpose of this full colour textbook is to put key data and published case studies of past climate change at your fingertips, so that you can experience the nature of paleoclimate reconstruction. Using foundational geologic concepts, students explore a wide variety of topics, including: marine sediments, age determination, stable isotope paleoclimate proxies, Cenozoic climate change, climate cycles, polar climates, and abrupt warming and cooling events, students are invited to evaluate published scientific data, practice developing and testing hypotheses, and infer the broader implications of scientific results. It is our philosophy that addressing how we know is as important as addressing what we know about past climate change. Making climate change science accessible is the goal of this book. This book is intended for earth science students at a variety of levels studying paleoclimatology, oceanography, Quaternary science, or earth-system science.s
Includes bibliographical references.; Index 476-485p.
Keywords: Climate changes; Earths climate history; Paleoclimatology; Geology